Negative pressure wound therapy for skin graft fixation: A reasonable option? - Meissner, Markus (Phlebologie, 2019)
Negative pressure wound therapy (NPWT) is meanwhile since about 20 years a standard procedure in classical wound care. Especially in wound ground conditioning of chronic wounds NPWT has an important status. In the last years, NPWT was more and more used in the fixation and postoperative wound management of skin grafts. The current review addresses the available data and evidence and demonstrates the possible use of the procedure.
Keywords: Negative pressure wound therapy; split thickness skin graft; chronic wound; randomized controlled study